Geoinformation systems use in the investigation of regional population growth - Кравченко, К. О. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2018)
Formulation of the problem. Use of GIS in socio-geographical studies determines their quality in our time. Due to the ability to display and analyze data, geographic information systems reveal the peculiarities of the spatial interaction of social and geographical objects. Use of GIS in the human geography to study population settlement systems allows us to establish patterns of formation and development in settlements and peculiarities of their distribution across the territory. The use of analytical capabilities of the GIS in the study of settlement systems helps to find out what determines the location of settlements and the link between them. The main stages of GIS analysis should be considered, such as questioning, evaluation of data, selection of the method of analysis, data processing and evaluation of the results.The purpose of the article. The purpose of this study is to uncover methodical bases for the use of geoinformation systems in the study of resettlement systems of the population in the region on the example of Kharkiv region in such GIS platforms as Map Info, Arc View, Arc Gis.Methods. The author’s own achievements as well as the research results of domestic and foreign investigators made the methodical basis for the article.Results. The article reveals the role of geoinformation systems in socio-geographical research, defines the main functions of geoinformation systems in the study of settlement systems, and presents an algorithm for conducting GIS analysis. Using geoinformation systems, the analysis of the resale structure of the region was carried out, advantages and disadvantages of methods of constructing population density maps of the region were identified, ways of constructing cartograms were presented. Features of constructing maps of demographic potential are presented in the article. The centrographic method is used for mathematical description of the spatial distribution of the population in the region. The topological methods of centrometry are presented. The advantages of using GIS in the research of resale systems are determined.Scientific novelty and practical significance. The article highlights the fact that when using GIS to construct cartographic images of the resettlement systems development, a combination of the spatial-temporal aspects of the research is important. One of the important advantages of the geoinformation approach in the study of resettlement systems is the operation of the attribute of objects, since a significant part of the derivatives of the geodemographic data given in the work (dynamics, density, percentages) were calculated by means of processing attributive information in GIS systems.Thus, using the GIS systems in the research of resale systems is explained by the need to establish spatiotemporal interconnections between settlements, to identify the features of the impact of the developed settlements on less developed, to determine the prospects for their further development and evolution of the system as a whole.